Uticaj globalizacije 4.0 i pandemije COVID-19 na pravnu regulativu i poslovanje malih i srednjih preduzeća unutar zemalja Evropske unije / The Impact of Globalization 4.0 and the COVID-19 Pandemic on the Legal Regulation and Business of Small and Medium-Sized Enterprises within the Countries of the European Union - Mahmutćehajić, Fatima; Silajdžić, Vedad; Berković, Amila (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
Globalization 4.0 as well as the global COVID-19 pandemic are two phenomena that have completely changed the world, including the way the business is done. The common assumptions that pandemics are slowing down the improvement of technologies have proven to be incorrect in the case of the COVID-19 pandemic, as it has spurred the growth of technologies to keep business running smoothly. As a percentage, 98% of European companies are small and medium-sized enterprises, which employ more than two thirds of the EU population. Moreover, economic and political processes that benefit from current political systems must improve industrial policies, laws, environmental policies and trade initiatives, by expanding the practice of designing multifunctional policies and integrating these policies. The Better Regulation Guidelines suggest making policies today for a better tomorrow. Evidence-based policy actions lh54 are constantly evaluated and improved if necessary, and are adopted transparently by informing all those concerned. The digital transformation is complex and rapidly evolving. Policy decisions and legal solutions become crucial. While progress has been made in addressing some of the most pressing and difficult political and legal issues facing governments today, more needs to be done to better understand some complex issues and design resilient policy and legal frameworks in response. The aim of this paper is to present the impact of globalization 4.0 and the COVID-19 pandemic on the legal framework for small and medium-sized enterprises within the European Union. In addition, measures and legal responses to mitigate the effects of COVID-19 on the operations of small and medium-sized enterprises within the European Union will be presented.